PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 011 PEMATANG INDAH KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Abdul Gapar; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve learning outcomes IPS Elementary School fifth grade students 011 Causeway Scenic District of Kelayang Indragiri Hulu in the academic year 2014/2015. The subjects were students of class V Elementary School 011 Pematang Indah totaling 14 people. Which consisted of 6 boys and 8 girls. This study is a Class Action Research (Classroom Actions Research) which comprises two cycles. Based on the results of research and data analysis known that there was an increase. In the first cycle, teachers earn an average of 72,91% success with good criteria. In the second cycle teachers earn an average of 91,67% success criteria very well. For the student activity during the implementation of cooperative learning model TPS, the implementation of the first cycle batting average gained 64,58% with a sufficient criterion. Implementation of the second cycle of activity students gain an average of 89,58% success criteria good. In addition, before implementation of cooperative learning model TPS is 61,79. Students who completed 6 people (42.86%) of 14 students. In the first cycle UH 1 daily value increased to 75,35 students who have increased as much as 21,94% the number of students who completed 9 students (64,28%) out of 14 students. In the second UH increased learning outcomes as much as 11,85% to 84.28. All students completed the implementation of the UH 2, meaning classical completeness of all students completed to 100%. It can be concluded that cooperative learning model TPS can improve learning outcomes of students in class V SD IPS 011 N Pematang Indah.Keywords: Cooperative Learning Model TPS, IPS Learning Outcomes